Regulation of the expression of key signalling molecules in mTOR pathway of skeletal muscle satellite cells in neonatal chicks: Effects of leucine and glycine–leucine peptide. Issue 3 (22nd March 2019) - She, Yue; Deng, Huiling; Cai, Huiyi; Liu, Guohua
Abstract: This study was conducted to analyse the effects of leucine (Leu) and glycine (Gly)‐Leu peptide on expressions of key signalling molecules in mTOR pathway of skeletal muscle satellite cells in neonatal chicks. The 4‐day‐old male AA broilers with similar weight were selected to obtain the broiler skeletal muscle satellite cells with the two‐step method of collagenase‐I and trypsin digestion. The satellite cells were subjected to primary culture in vitro, and they were cultured in DMEM medium with the Leu concentration of 0.2 mM and 2 mM as well as with the Gly‐Leu peptide concentration of 0.2 mM and 2 mM. The experiment lasted for 5 days. The results showed that TOR, S6K1 and 4E‐BP1 mRNA expressions in the medium with Leu concentration of 2 mM were significantly higher than that in 0.2 mM group ( p < 0.05). There was no difference between the medium with Gly‐Leu concentration of 2 mM and 0.2 mM on the TOR, S6K1 and 4E‐BP1 mRNA expressions ( p > 0.05). In conclusion, Leu significantly increases TOR, S6K1 and 4E‐BP1 mRNA expressions of skeletal muscle satellite cells, but Gly‐Leu peptide has no effect on them.